Les filles d’Hannah Arendt, les « sœurs de solitude » dans l’arène politique antillaise - Max Belaise (Études Caribéennes)
The view that women have of themselves and of the world undoubtedly conditions their commitments to the “Republic of males”. In its list of priorities, the Caribbean woman does not exhibit a militant commitment to sex equality. Certainly, the cultural context in which women live does not encourage this stance. Nevertheless, paradoxically, Caribbean women are able to succeed and prosper in the business world. Perhaps a long tradition of resourcefulness for the survival of her offspring and of herself, in other words for the oikonomia, constitutes the basis for such an economic competence. Introduction